Social Cultural Changes and Development of Indonesian Society by Using Communications Technology - Hidayat Rastami, Mhd. Ilham; Ivana, Julia (Berpusi Publishing, 2023)
The development of this communication technology is the current information material has reached the level of need for every community around the world. not only in its use as a channel of information communication between individuals in social interactions, but also in a wider scope between institutions and other institutions, between regions and regions to countries and continents. Indonesian culture, which is a marriage of all national cultures, has experienced a process of interaction and acculturation for a long time to form a new culture. It is this technology that helps and provides convenience in terms of aspects of people's lives and increases productivity, but also creates problems or impacts on the culture itself. Triggering the level of change and shift in lifestyle from patterns that rely on direct communication to communication using the media, the displacement of local wisdom in the context of customs and wider culture. This journal discusses how Islam as a source of values ​​and teachings for its people encapsulates all the desires and rules of life of its adherents. Technology and culture grow and develop along with the progress of civilization which has the concept of religion and state. How does this concept become an urgent part of socio-cultural change in relation to Islamic da'wah and the benefit of the people? This journal discusses how Islam as a source of values ​​and teachings for its people encapsulates all the desires and rules of life of its adherents. Technology and culture grow and develop along with the progress of civilization which has the concept of religion and state. How does this concept become an urgent part of socio-cultural change in relation to Islamic da'wah and the benefit of the people? This journal discusses how Islam as a source of values ​​and teachings for its people encapsulates all the desires and rules of life of its adherents. Technology and culture grow and develop along with the progress of civilization which has the concept of religion and state. How does this concept become an urgent part of socio-cultural change in relation to Islamic da'wah and the benefit of the people.